2010
DOI: 10.1155/2010/418695
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Parathyroid Hormone on Immune Function

Abstract: Parathyroid hormone (PTH) function as immunologic mediator has become interesting with the recent usage of PTH analogue (teriparatide) in the management of osteoporosis. Since the early 1980s, PTH receptors were found on most immunologic cells (neutrophils, B and T cells). The in vitro evaluations for a possible role of PTH as immunomodulator have shown inconsistent results mainly due to methodological heterogeneity of these studies: it used different PTH formulations (rat, bovine, and human), at different dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 76 publications
0
40
0
1
Order By: Relevance
“…Increases in intracellular calcium levels potentially lead to an increase in cellular adenylate cyclase activity; this has been proposed as the mechanism by which PTH influences leukocytes. However, the effects of PTH on T lymphocytes are neither consistent nor conclusive (Geara et al 2010). Most studies showed that PTH exerts an inhibitory effect on various immune system parameters, while other studies showed that PTH has a stimulatory function.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Increases in intracellular calcium levels potentially lead to an increase in cellular adenylate cyclase activity; this has been proposed as the mechanism by which PTH influences leukocytes. However, the effects of PTH on T lymphocytes are neither consistent nor conclusive (Geara et al 2010). Most studies showed that PTH exerts an inhibitory effect on various immune system parameters, while other studies showed that PTH has a stimulatory function.…”
Section: Discussionmentioning
confidence: 94%
“…There is a direct correlation between PTH levels in uremic patients and the degree of lymphocyte proliferation inhibition in ESRD patients with SHP; PTH has been identified as a possible factor in the development of an acquired immune dysfunction (ShurtzSwirski et al 1995). PTH receptors are found on most immunologic cells (neutrophils, B cells, and T cells), suggesting a potential role for PTH in immune system regulation (Geara et al 2010). Increases in intracellular calcium levels potentially lead to an increase in cellular adenylate cyclase activity; this has been proposed as the mechanism by which PTH influences leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Correlations between VZV immunoglobulin and mineral bone parameters were analyzed owing to anecdotal evidence regarding the impact of hyperparathyroidism on immune system, and calcium related VZV gene regulation2223. VZV-IgG levels were negatively associated with the presence of malignancy ( p = 0.02), marginally associated with male gender ( p = 0.06), whereas VZV-IgM levels were positively associated with higher hemoglobin levels ( p = 0.05) but negatively associated with the presence of heart failure in chronic dialysis patients ( p = 0.04).…”
Section: Resultsmentioning
confidence: 99%
“…dysfunction. 133,134 Furthermore, a very recent study showed that in 5/6 nephrectomized mice, PTH induced adipose tissue browning and cachexia and, thereby, presumably induced skeletal muscle atrophy. 135 Thus, there are multiple mechanisms linking the physiological response for maintaining phosphate homeostasis with adverse clinical outcomes.…”
Section: Toxicity Of Excess Phosphatementioning
confidence: 99%